Applications of regenerative medicine in Stomatology - Denia Morales Navarro (Editorial Ciencias Médicas, 2014)
Introduction: Nowadays, one of the most outstanding medical issues is to regenerative medicine and in particular stem cells, which has been described as a new scientific and technological revolution. Objective: to review the literature on applications of regenerative medicine in Stomatology. Procedures employed in the collection of information: We performed a review in the period July 2013 and August 2013. Impact journals were evaluated Web of Sciencies related to this topic (50 journals) and 2 Cuban magazines. Were consulted databases referativos systems such as MEDLINE , PubMed and SciELO with the use of descriptors such as " tissue engineering dentistry ", " regenerative medicine", "biomaterials" , "scaffolds" , "oral regeneration" and their Spanish counterparts . We included articles in English and Spanish and publications of the last five years. 171 articles were obtained, confined the study to 52 that focused this issue more comprehensively. 5 books were reviewed. Results: Analysing the behavior of the articles on the subject of study with respect to their representation in the various scientific journals where they were published, 5.8 % of them corresponded to the journal Tissue Engineering. Part B, Reviews. The remaining items were evenly distributed among the other magazines. Conclusions: applications of regenerative medicine in the dental field are surprisingly versatile and tissue regeneration capacity as dicímiles as dental and periodontal soft tissues of the craniofacial region by creating vascularized prefabricated flaps , wound treatment , regeneration cartilage of the temporomandibular joint, tongue, skin, mucous membranes, nerves, vessels and salivary glands which is an excellent alternative for the care of multiple congenital or acquired disorders in the maxillofacial area.